Back Cover: Chemical Mapping by Macroscopic X‐ray Powder Diffraction (MA‐XRPD) of Van Gogh's Sunflowers: Identification of Areas with Higher Degradation Risk (Angew. Chem. Int. Ed. 25/2018). Issue 25 (2nd May 2018) - Vanmeert, Frederik; Hendriks, Ella; Van der Snickt, Geert; Monico, Letizia; Dik, Joris; Janssens, Koen
Abstract : Sunflowers one of the iconic works of Van Gogh, contains two different chrome yellow pigments: the light‐fast monoclinic PbCrO4 (crocoite), and the light‐sensitive monoclinic PbCr1‐ x S x O4 ( x ≈0.5). In their Communication onpage 7418 ff., F. Vanmeert et al. describe how they visualized the distribution of these two pigments throughout the painting's surface using macroscopic X‐ray powder diffraction scanning. In this manner, areas that are at risk of darkening were identified.